The role of the Russian language in the modern world - Nargiza Akhmadjonovna Baratova (Science and Education, 2024)
The Russian language not only connects peoples, but also serves as an important tool in preserving cultural heritage. It provides access to the richest literature, music and art, which promotes cultural exchange and mutual understanding. In the field of science, the Russian language also has a significant influence. It is used in a number of scientific studies and publications, especially in fields such as physics, biology, chemistry, mathematics and astronomy. And Russian continues to be an important global resource that promotes dialog between cultures and supports the diversity of the world’s linguistic space.